Soviet Reforms and Beyond - Cooper, Leo. author. aut Link
VIII, 190 p.
Keywords: Since Gorbachev came to power much has happened in the Soviet Union. This book provides a comprehensive and composite analysis of the reforms that have taken place in the Soviet Union since 1985.